2008
DOI: 10.2337/db07-0599
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Diet-Induced Obesity and Improved Insulin Sensitivity in Mice With a Regulator of G Protein Signaling–Insensitive G184S Gnai2 Allele

Abstract: RGS proteins and G alpha(i2) signaling play important roles in the control of insulin sensitivity and glucose metabolism. Identification of the specific RGS proteins involved might permit their consideration as potential therapeutic targets for obesity-related insulin resistance and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 48 publications
1
37
0
1
Order By: Relevance
“…Interestingly, in another previous study, knock-in mice expressing RGS-insensitive G i␣2 also exhibited lower body weights and smaller fat stores than control mice (14). However, the phenotype was significantly blunted after backcrossing into another mouse strain (14). Together, these results demonstrate critical roles of RGS proteins and G i␣2 in the control of body weight and metabolism, although their impact is modulated by the genetic background of the mice.…”
Section: Generation Of Rgs5mentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, in another previous study, knock-in mice expressing RGS-insensitive G i␣2 also exhibited lower body weights and smaller fat stores than control mice (14). However, the phenotype was significantly blunted after backcrossing into another mouse strain (14). Together, these results demonstrate critical roles of RGS proteins and G i␣2 in the control of body weight and metabolism, although their impact is modulated by the genetic background of the mice.…”
Section: Generation Of Rgs5mentioning
confidence: 57%
“…In a previous study, the levels of Rgs5 mRNA in the inguinal adipose tissue of C57BL/6J males were higher in high weight gainers than in low weight gainers after 4 weeks on a high-saturated-fat diet (http://www .ncbi.nlm.nih.gov/projects/geo/gds/profileGraph.cgi?&data setϭAYGzxl&datasetϭmpnsrq$&gminϭ48681.000000 &gmaxϭ96279.000000&abscϭ&gdsϭ2319&idrefϭ401103 &annotϭRgs5). Interestingly, in another previous study, knock-in mice expressing RGS-insensitive G i␣2 also exhibited lower body weights and smaller fat stores than control mice (14). However, the phenotype was significantly blunted after backcrossing into another mouse strain (14).…”
Section: Generation Of Rgs5mentioning
confidence: 98%
“…These mice show dramatic phenotypes, including resistance to diet-induced obesity and antidepressant-like behavioral effects (Huang et al, 2006(Huang et al, , 2008Talbot et al, 2010). RGS4 is upregulated in the dorsal horn of spinal cord during the development of neuropathic pain (Garnier et al, 2003), and RGS4 can inhibit several pain-modulating receptors (e.g., -opioid receptor) (Garnier et al, 2003;Traynor and Neubig, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This "RGS-insensitivity" point mutation (glycine to serine) was originally identified by DiBello et al (1998) in GPA1, the G␣ subunit of the yeast S. cerevisiae, functions equivalently in mammalian G␣ subunits such as G␣ i1 , G␣ o , and G␣ q (Lan et al, 1998;Clark and Traynor, 2004) and has also been shown to leave all other functions of G␣ intact, including intrinsic nucleotide binding and hydrolysis activities, as well as coupling to G␤␥, receptor, and effectors (Lan et al, 1998;Chen et al, 2004;Day et al, 2004;Fu et al, 2004;Ikeda and Jeong, 2004). Separate mouse strains bearing this RGS-insensitivity point mutation (G184S) within their G␣ o or G␣ i2 gene loci, respectively, have been generated (Fu et al, 2004;Huang et al, 2006); these mice possess select changes in various organ system functions controlled by GPCR signaling, including central nervous system, cardiovascular, and endocrine functions (Fu et al, , 2007Huang et al, 2006Huang et al, , 2008Goldenstein et al, 2009;Icaza et al, 2009;Signarvic et al, 2010;Talbot et al, 2010). The most recent findings of Ruiz de Azua et al (2010), that RGS4 is a negative regulator of M3 mAChR signaling to insulin secretion in pancreatic ␤-cells, articulate well with the findings of Huang et al (2008) that RGS-insensitive G␣ i2 (G184S) knock-in mice exhibit increased glucose tolerance when on a high-fat diet.…”
Section: A the Utility Of The "Regulators Of G-protein Signaling-insmentioning
confidence: 99%
“…Separate mouse strains bearing this RGS-insensitivity point mutation (G184S) within their G␣ o or G␣ i2 gene loci, respectively, have been generated (Fu et al, 2004;Huang et al, 2006); these mice possess select changes in various organ system functions controlled by GPCR signaling, including central nervous system, cardiovascular, and endocrine functions (Fu et al, , 2007Huang et al, 2006Huang et al, , 2008Goldenstein et al, 2009;Icaza et al, 2009;Signarvic et al, 2010;Talbot et al, 2010). The most recent findings of Ruiz de Azua et al (2010), that RGS4 is a negative regulator of M3 mAChR signaling to insulin secretion in pancreatic ␤-cells, articulate well with the findings of Huang et al (2008) that RGS-insensitive G␣ i2 (G184S) knock-in mice exhibit increased glucose tolerance when on a high-fat diet.…”
Section: A the Utility Of The "Regulators Of G-protein Signaling-insmentioning
confidence: 99%